MODEL IMPLEMENTASI DESA WISATA BERBASIS MASYARAKAT DI DESA WISATA MUNGGU KABUPATEN BADUNG BALI - Ni Wayan Mekarini; I Wayan Kartimin (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2023)
The research entitled The Implementation of Community Based Tourism Model in Munggu Village Badung Bali focused on how Munggu tourist village manage the local tourist potencies based on community participation. Data collected by observation and deep interview with village leaders and Pokdarwis (local tourism management) Head. Though the status as tourist village for Munggu village is given in 2010 with 10 other villages in Badung Regency but the follow up run slowly until the new Pokdarwis Leader make a visit to Tourist Board of Badung Regency who give a slight understanding. Then, the community-based management is implemented start from village legality, local people representative, socialization program to stakeholders, people chance for getting job, collaboration with BumDes (Commercial Village Board) as well as receiving profit through legal institution. In the program of managing Munggu Beach, Pokdarwis team held some preparations, such as cleanliness, placing food stall, parking area, toilet, information desk with healthy protocol aids. The source of fund come from food stall retribution and parking ticket. Later, it is divided 45% for BumDes after taking some for operational and depreciation. It means that the profit is shared to people through relevant institution where as another 5% for donation and education program. In short, Munggu Tourist Village successfully implemented community-based tourism management which is similar to village management model in Bali